Química y Farmacología de Smallanthus sonchifolius (Poepp.) H. Rob. (“Yacón”) - Lock, Olga (2005)
This review article covers the present knowledge on the chemistry and biological activities of Smallanthus sonchifolius (Poepp.) H. Rob. A description of the chemical compounds reported in the scientific literature (i.e. oligofructans, phenolic compounds and terpenes) is included. The biological activities of the crude extracts of leaves and roots from yacón are discussed.